2021
DOI: 10.3389/fpls.2021.704262
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic, Proteomic, and Metabolic Profiles of Catalpa bungei Tension Wood Reveal New Insight Into Lignin Biosynthesis Involving Transcription Factor Regulation

Abstract: Lignin is a complex polymer in plant cell walls whose proportion is second only to that of cellulose and plays an important role in the mechanical properties of wood and stress resistance of plants. Here, we induced tension wood (TW) formation in Catalpa bungei by artificial bending and analyzed the lignin metabolism of the TW. LC-MS analysis showed that a significantly higher content of coniferyl aldehyde was observed in the TW cell wall than in the opposite wood (OW) and normal wood (NW) cell walls. TW had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…The regulatory relationship between candidate TFs and the seven target genes was shown in Figure 9 . The node degree of TFs was defined as the number of target genes one TF may regulate, which could represent the importance of TFs in the metabolic pathway ( Xiao et al., 2021 ). The results showed that each TF had several target genes with a node degree ranging from 1 to 5 ( Table 4 ; Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulatory relationship between candidate TFs and the seven target genes was shown in Figure 9 . The node degree of TFs was defined as the number of target genes one TF may regulate, which could represent the importance of TFs in the metabolic pathway ( Xiao et al., 2021 ). The results showed that each TF had several target genes with a node degree ranging from 1 to 5 ( Table 4 ; Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to transcriptomics or proteomics, metabolomics is an emerging omics technology aimed at identifying and quantifying endogenous molecule metabolites, the final products of cell biological regulation process ( Lin et al., 2020 ). In recent years, “multi-omics” strategies have provided new insights in revealing underlying mechanisms in plant growth and development as well as in plant responses to external stresses ( Xiao et al., 2021 ; Zhang et al., 2021c ; Li et al., 2022a ; Wang et al., 2022b ). The combined analysis of transcriptome and metabolome data can be used to predict the gene function involved in the targeted metabolic pathway and simultaneously provide supporting information for gene mining ( Fukushima et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, TW formation in angiosperms has a high cellulose content and is formed in the upper side of an inclination of a stem [ 12 ]. Recently, many studies have been conducted on TW formation in various angiosperm species, including Catalpa bungee , Populus trichocarpa , Hevea brasiliensis , and Betula luminifera , to understand the underlying molecular mechanisms and identify essential genes [ 14 , 15 , 16 , 17 , 18 ]. Previously, Sato et al [ 19 ] reported transcriptome analysis of reaction wood formation from Chamaecyparis obtusa .…”
Section: Introductionmentioning
confidence: 99%